Facile fabrication of hydroxyapatite-magnetite-bentonite composite for efficient adsorption of Pb(II), Cd(II), and crystal violet from aqueous solution. (20th February 2020) - Ain, Qurat Ul; Zhang, Hanbing; Yaseen, Muhammad; Rasheed, Usman; Liu, Kun; Subhan, Sidra; Tong, Zhangfa
Abstract: This study reports a facile fabrication route for hydroxyapatite (HAp) nanoparticles impregnated magnetic bentonite (HAp@Fe3 O4 @bentonite) composite, which was in turn applied for the removal of Pb(II), Cd(II) and crystal violet (CV) dye from aqueous solution. Adsorption isotherm data best fitted with Freundlich isotherm model and kinetic behavior adopted pseudo-second order adsorption mechanism attaining equilibrium in 60 min over a wide pH range (2.0–13). HAp@Fe3 O4 @bentonite was magnetically separable and realized higher adsorption capacity for Pb(II) (404.56 mg/g), Cd(II) (310.36 mg/g) and CV (1201.30 mg/g) than those of acid-treated bentonite (161.28, 155.7 and 740.14 mg/g, respectively). Similarly, the higher Langmuir maximum adsorption capacity exhibited by HAp@Fe3 O4 @bentonite for Pb(II), Cd(II) and CV (482, 309 and 1290 mg/g respectively) was attributed to –OH, NH2, PO4 3− surface functionalities. Fresh and spent adsorbents were characterized by Fourier transform infra-red (FTIR) spectroscopy, X-ray diffraction (XRD), differential thermogravimetry, Brunauer–Emmett–Teller (BET) surface area analysis, scanning electron microscopy, energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and vibrating-sample magnetometry techniques. HAp@Fe3 O4 @bentonite composite exhibited BET surface area of 73.72 m 2 /g, pore volume of 0.026 cm³/g and an average particle size of 81.39 nm. The composite remained active for five successive adsorption reuses with minimal loss in adsorption capacity as confirmed by FTIR and XRD analyses. The newly synthesized HAp@Fe3 O4 @bentonite composite possessing high adsorption efficiency for Pb(II), Cd(II) and CV can be envisaged as a promising solution for wastewater treatment. Graphical abstract: Image 1 Highlights: Hydroxyapatite-impregnated magnetite-bentonite composite was synthesized. Adsorption capacity for Pb(II) (482 mg/g) and Cd(II) (309 mg/g) was achieved. Composite remained stable in pH range 2.0–13.0 and was thermally stable. Enhanced adsorption of composite was due to -OH -, -PO4 3- and –NH2 surface groups.